Seasonal diet of guanaco (Lama guanicoe) linked to vegetation life forms and environment types in Tierra del Fuego (Argentina) - Soler, R.; Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Borrelli, L.
Large diversity of habitat types, plant species assemblages, and silvopastoral activities in Nothofagus spp. forests condition the food availability for native herbivores. This work evaluates the seasonal diet of Lama guanicoe linked to plant life forms and habitat types in sub-Antarctic forests. The study evaluated vegetation availability and habitat types by floristic surveys (n = 206) in Tierra del Fuego, and seasonal diet of L. guanicoe by a micro-histological analysis of feces (n = 4 in four areas, during four season). Open lands showed the highest plant richness, while lowest values corresponded to primary Nothofagus pumilio forests. Nothofagus pumilio (21.6 %), Carex spp. (17.2 %), Misodendrum spp. (10.6 %) and Deschampsia spp. (8.6 %) were the most frequent items found in feces. Significant differences were seasonally found in diet composition and trophic niche breadth: grasses were all consumed along the year, while tree browsing decreased and the proportion of shrubs increased in winter. This study highlights the widespread use of different habitats by guanaco, including harvested forests. In summer and spring Nothofagus spp. forests were the main source of food for guanacos, depending more on open lands during winter. The knowledge of plant-native herbivores interactions in productive landscapes could improve the management plans towards an ecologically sustainable strategy. Fil: Soler, R. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Cientificas; Argentina; Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Cientificas; Argentina; Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Cientificas; Argentina; Fil: Borrelli, L. Instituto Nacional de Tecnologia Agropecuaria; Argentina;